Differences within the mainland Chinese press: a quantitative analysis. Issue 2 (4th March 2017) - Wang, Haiyan; Sparks, Colin; Lü, Nan; Huang, Yu
ABSTRACT: This paper reports the results of a content analysis of five newspapers selected from the Chinese daily press. The research was conducted as part of an international project designed to explore the relationship between journalistic self-conceptions and journalistic practice. This paper reports only upon journalistic practice, in particular the extent to which different models of journalism are present. The results of the analysis demonstrate, firstly, that while the concept of a uniform 'national media system' is of some utility in comparative studies, there are, even in the highly structured Chinese case, very significant differences within a single country. Secondly, it demonstrates that the common division of the Chinese press into a politically oriented party press and a market-oriented commercial press is inadequate to explain the identifiable differences between titles in the sample. A four grouping solution fits the data much better and demonstrates that there are newspapers that combine strong evidence of indicators of the party press with strong evidence of indicators of the commercial press. As a consequence, the claim that marketization will necessarily lead to conflicts with the party appears to be mistaken.